(untitled) (Journal of Atomic and Molecular Sciences, 2011)
Reaction mechanism of OH radical and ethane has been investigated by using ab initio (MP2) and hybrid DFT (B3LYP and BH&HLYP) methods with 6-311++G(d,p) basis set. The MP2 method can provide more reasonable geometrical structures than the B3LYP and BH&HLYP DFT functionals. The methodology does not significantly alter vibrational frequencies. Compared with previous reports, at MP2 level, large basis set is necessary to predict the barrier heights and reaction energies. Spin-projected MP2 energies with 6-311++G(d,p) basis set were adopted to construct the potential energy surface. Hydrogen abstraction channel exhibits most exothermicity and lowest barrier height. This channel is predominant thermodynamically and kinetically, and proceeds via an "early" transition state. The other channels are minor and their transition-state structures are neither reactant-like nor product-like.